Motorcycle Ownership Assessment and Estimation in Makurdi, North Central, Nigeria: A Multinomial Logit Model Approach - Gbagir, K.; Etu, J. E.; Oyedepo, O. J. (Journal of Civil Engineering, Science and Technology, 2018)
With the rapid rise in problems associated with use of motorcycles as alternative means to inadequate public transportation, this study seeks to identify household factors influencing motorcycle ownership in Makurdi. The study estimates the influence of the various household factors identified and a model for predicting motorcycle ownership is developed for the study area. Data were collected via a questionnaire survey of 1412 households in the study area. The survey revealed that the number of motorcycles owned per household in the low density zone was 0.67 while that for the medium and high density zones was 0.62 and 0.79 respectively. The multinomial logit model developed predicted that 67% of households owned motorcycles as compared to 71% observed from survey data. Severity applications of the model to test the effects of changing economic situations on motorcycle ownership showed that residents of the study area are more disposed to owning motorcycles in periods of recession than periods of economic boom. The study gives an understanding of motorcycle growth pattern and ownership characteristics in the study area and will therefore serve as a relevant input for planning, regulation and control of motorcycle activities in the study area.